2006
DOI: 10.1177/1359105306066615
|View full text |Cite
|
Sign up to set email alerts
|

‘When Suppression Backfires’

Abstract: Based on Wegner's Ironic Processing Theory, this study examines the effects of suppressing eating-related thoughts in a sample of 77 female students. A distinction was made between disinhibited restrainers (high dietary restraint/high disinhibition), inhibited restrainers (high dietary restraint/low disinhibition) and low restrainers. Results indicate that disinhibited restrainers used thought suppression more often and were the only group to show a rebound effect for eating-related thoughts after suppression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The nascent research investigating the relationship between thought suppression and eating behaviors have reported mixed findings. Some studies [3,4,5,6,7] found that the outcomes of thought suppression, such as hyperaccessibility and rebound, do result from attempting to suppress food-related thoughts, whereas one study did not [8,9,10]. The latter study, however, [8] did not examine if the outcomes of thought suppression differed between participants who were currently dieting versus not or healthy weight versus overweight/obese, both of which appear to affect the outcomes of thought suppression [11–13].…”
mentioning
confidence: 99%
“…The nascent research investigating the relationship between thought suppression and eating behaviors have reported mixed findings. Some studies [3,4,5,6,7] found that the outcomes of thought suppression, such as hyperaccessibility and rebound, do result from attempting to suppress food-related thoughts, whereas one study did not [8,9,10]. The latter study, however, [8] did not examine if the outcomes of thought suppression differed between participants who were currently dieting versus not or healthy weight versus overweight/obese, both of which appear to affect the outcomes of thought suppression [11–13].…”
mentioning
confidence: 99%
“…Researchers recently started examining the relationship between thought suppression and eating and weight (e.g., Hooper, Sandoz, Ashton, Clarke, & McHugh, 2012). The literature, however, was limited to the WBSI (e.g., Soetens, Braet, Dejonckheere, & Roets, 2006). To address this limitation, researchers created the Food Thought Suppression Inventory (e.g., “I have thoughts about food that I try to avoid;” Barnes & Tantleff-Dunn, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…The little existing research examining the association between thought suppression and eating behaviors has resulted in mixed findings. The consequences of thought suppression, such as hyperaccessibility and rebound, have been found to result from attempting to suppress food-related thoughts in some studies (Dejonckheere, Braet, & Soetens, 2003; Smart & Wegner, 1999; Soetens & Braet, 2006; Soetens, Braet, Dejonckheere, & Roets, 2006; Soetens, Braet, & Moen, 2008) but not all (May, Andrade, Batey, Berry, & Kavanagh, 2010; Soetens & Braet, 2007; Soetens, Braet, & Bosmans, 2008). Of note is that May et al (2010) did not consider dieting status or weight in their analyses, both of which may influence thought suppression (e.g., Erskine & Georgiou, 2010; Kemps, Tiggemann, & Christianson, 2008; O'Connell, Larkin, Mizes, & Fremouw, 2005; Pop, Miclea, & Hancu, 2004; Soetens et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Soetens et al, 2006) were limited to the White Bear Suppression Inventory (WBSI), a self-report measure of general thought suppression. To address the limitation that eating-related studies were restricted to a general measure of thought suppression, rather than one specific to eating, researchers recently created the Food Thought Suppression Inventory (FTSI), which was validated with non-clinical samples of women (Barnes, Fisak, & Tantleff-Dunn, 2010) and men (Barnes & White, 2010).…”
Section: Introductionmentioning
confidence: 99%